(untitled) - Quintanilla, Kelly M. (Thousand Oaks, Calif, 2014)
This text presents an exciting new approach to teaching the core concepts and techniques of business and professional communication, and is organized by the sequence readers will face as they transition from student to professional life, giving them the skills they need to move from interviewee to team member to leader
Keywords: Business communication,Giao tiếp thương mại